Water Witching - Jim Hoy (Symphony in the Flint Hills, 2018)
Introduction: Back during the drouth of the 1950s we were able to nurse our well at the house just enough to get by, but the windmill in the corral by the barn was having trouble keeping up with the horses and mules, so Dad decided to have another well drilled. By the time it was all over, drillers had put down five holes for us, including three in nearby pastures. The trouble is that here in the Flint Hills veins of ground water are unpredictable.